Hunger for justiciability and judicial eligibility claiming the human rights to adequate food before Philippine Courts notes (Philippine Law Journal, 2020)
Can a human right without textual basis in the 1987 Constitution be demandable and actionable before Philippine courts of justice? The human right to adequate food is not provided in the 1987 Constitution, and the Philippine legislature has yet to enact specific legislation to institutionalize a framework for such right. The Philippines, however, is a state-party to a number of international human rights treaties and conventions that recognize the right to adequate food. As such, the Philippines is duty-bound to apply these international instruments domestically and to observe the obligations created under such multilateral agreements. The present legal architecture brings to light the challenge of judicial enforceability of the right to adequate food in case infractions are committed or obligations are neglected. Grounded on the premise that a human right, to be complete and fully realized, must have the capacity to be claimed by right-holders and the capacity to hold duty- bearers accountable, this paper attempts to determine whether the unwritten human right to adequate food is justiciable and judicially exigible, and more importantly, how it can be legally actionable before domestic courts.